Respuesta :
Step-by-step explanation:
1) zeros of the given function:
6x²-3=0; ⇔ 6(x²-0.5)=0; ⇔ x²=0.5; ⇔
[tex]\left[\begin{array}{ccc}x=-\sqrt{0.5} \\x=\sqrt{0.5} \end{array}[/tex]
2) relationship:
if to see the equation x²-0.5=0 (ax²+bx+c=0 is standart form!), then the sum of the zeros is '0' (it is 'b' of the standart form), the product of equation roots is '-0.5' (it is 'c' of the standart form).
[tex]{\large{\textsf{\textbf{\underline{\underline{Given :}}}}}}[/tex]
★ The polynomial
f(x) = 6x² - 3
[tex]{\large{\textsf{\textbf{\underline{\underline{To \: find :}}}}}}[/tex]
★ Zeroes of the polynomial f(x) = 6x² - 3
[tex]{\large{\textsf{\textbf{\underline{\underline{Solution :}}}}}}[/tex]
We have,
[tex]f(x) = \tt 6 {x}^{2} - 3[/tex]
Which can also be written as
[tex] \implies f(x) = \tt {(\sqrt{6} x)}^{2} - { (\sqrt{3}) }^{2} [/tex]
Using a² - b² = (a - b) (a + b)
[tex] \implies f(x) = \tt ( \sqrt{6} x - \sqrt{3} )( \sqrt{6} x + \sqrt{3} )[/tex]
To find the zeroes, solve f(x) = 0
[tex] \longrightarrow \tt ( \sqrt{6} x - \sqrt{3} )( \sqrt{6} x + \sqrt{3} ) = 0[/tex]
either [tex] \tt \sqrt{6} x - \sqrt{3} = 0 \: or \: \sqrt{6} x + \sqrt{3} = 0[/tex]
[tex] \implies \tt \sqrt{6} x = \sqrt{3 \: } \: or \: \: \sqrt{6} x = - \sqrt{3}[/tex]
[tex] \implies \tt x = \dfrac{ \sqrt{3} }{ \sqrt{6} } \: or \: x = - \dfrac{ \sqrt{3} }{ \sqrt{6} }[/tex]
[tex] \implies \tt x = \dfrac{ \sqrt{3} }{ \sqrt{2 \times 3} } \: or \: x = - \dfrac{ \sqrt{3} }{ \sqrt{2 \times 3} }[/tex]
[tex]\implies \tt x = \dfrac{ \cancel{ \sqrt{3} }}{ \sqrt{2} \: \cancel{\sqrt{3}} } \: or \: x = - \dfrac{ \cancel{ \sqrt{3} }}{ \sqrt{2} \: \cancel{\sqrt{3}} }[/tex]
[tex]\implies \tt x = \dfrac{1}{ \sqrt{2} } \: \: or \: \: - \dfrac{1}{ \sqrt{2} }[/tex]
Hence, the zeroes of f(x) = 6x² - 3 are:
[tex] \tt \alpha =\sf \boxed {{ \red{ \dfrac{1}{ \sqrt{2} } } }}\: \: and \: \: \beta =\sf \boxed {{ \red{ - \dfrac{1}{ \sqrt{2} } } }}[/tex]
• Verification
Sum of zeroes = [tex] ( \alpha + \beta )[/tex]
[tex] = \tt \dfrac{1}{ \sqrt{2} } + \bigg(- \dfrac{1}{ \sqrt{2} } \bigg)[/tex]
[tex] = \tt \dfrac{1}{ \sqrt{2} } + - \dfrac{1}{ \sqrt{2} } [/tex]
[tex]= \tt 0[/tex]
and, [tex]\tt - \dfrac{Coefficient \: of \: x}{Coefficient \: of \: {x}^{2} }[/tex]
[tex] \tt = - \dfrac{0}{6} [/tex]
[tex] \tt = 0[/tex]
[tex] \therefore \tt \: Sum \: of \: zeroes = {\boxed{ \red{\dfrac{ \tt Coefficient \: of \: x}{ \tt Coefficient \: of \: {x}^{2}}}}}[/tex]
Also,
Product of zeroes = [tex] \alpha \beta [/tex]
[tex] = \dfrac{1}{ \sqrt{2} } \times - \dfrac{1}{ \sqrt{2} } [/tex]
[tex] = - \dfrac{1}{ 2 } [/tex]
and, [tex]\tt - \dfrac{Constant \: term}{Coefficient \: of \: {x}^{2} }[/tex]
[tex] \tt = \dfrac{ - 3}{6} [/tex]
[tex] \tt = \dfrac{ - 1}{2} [/tex]
[tex] \therefore \tt \: Product \: of \: zeroes = {\boxed{ \red{\dfrac{ \tt Constant \: term}{ \tt Coefficient \: of \: {x}^{2}}}}}[/tex]
[tex]\rule{280pt}{2pt}[/tex]